Morphofunctional characterization of elderly women according to depressive symptomatology - Guimaraes, Sônia Merian; Silva, Cristiano Garcia da; Rica, Roberta Luksevicius; Maia, Adriano Fortes; Alonso, Angélica Castilho; João, Gustavo Alegretti; Ceschini, Fabio; Bocalini, Danilo Sales (Manual Therapy, Posturology & Rehabilitation Journal, 2019)
Introduction: Aging is an irreversible physiological process that promote changes on biological parameters that culminate in limitations in the execution of daily tasks Objective: Evaluate the morphofunctional parameters of the elderly with and without depressive symptomatology. Methods: A cross-sectional descriptive exploratory study was carried out using the protocol of evaluation of the functional autonomy of the Latin American Development Group for Maturity (GDLAN Protocol), consisting of walking 10 meters (C10m), rising from the sitting position (LPS), rising from the ventral position (LPDV) and rising from a chair and moving around the house (LCLC). Results: No significant differences (p>0.05) were found between the groups on functional tests and anthropometric parameters, however, statistical differences (p = 0.001) were found between the groups in the general GDLAM index. Additionally, a positive correlation (r2 : 0.778; p<0.01) was observed between the scores of depressive symptomatology and the general index GDLAM indicating that impairments in functional fitness proportionally higher incidence of depressive symptoms. Conclusion: The results suggest that elderly women with a depressive symptom present lower physical fitness than elderly women without symptoms of depression, and that physical activity is necessary for both samples to contribute to the improvement of daily life activities.